2015
DOI: 10.1158/1535-7163.mct-14-0625
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Regulated microRNA-125–HER2 Pathway as a Novel Therapeutic Target for Trastuzumab-Mediated Cellular Cytotoxicity in Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) accounts for 15% of all lung cancer cases and is a highly lethal disease. For the last several decades, the standard treatment for SCLC has been deadlocked, and new therapeutic strategies are urgently needed. HER2 is a member of the HER family and has been reported to be overexpressed in 30% of SCLC cases with poor prognosis. However, the clinical relevance of HER2-targeted therapy for SCLC remains unclear. Here, we first identify that cytotoxic drugs induce significant HER2 overe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…Our study showed that no miRNA was different between males and females in adenoma-free mice, while 3 miRNAs (miR-10a, miR-125, and miR-130a) were differentially expressed in adenoma-bearing male and female mice. In particular, miR-10a is related to estrogen dependent cancer promotion [112, 113], miR-130a both to the estrogen and HER2 pathways [114, 115], and miR-125 to HER2/erbb2 estrogen sensitive oncogene activation [116, 117]. These findings support the view that estrogen and HER2-dependent mechanisms can contribute to CS-induced lung carcinogenicity in females.…”
Section: Discussionmentioning
confidence: 62%
“…Our study showed that no miRNA was different between males and females in adenoma-free mice, while 3 miRNAs (miR-10a, miR-125, and miR-130a) were differentially expressed in adenoma-bearing male and female mice. In particular, miR-10a is related to estrogen dependent cancer promotion [112, 113], miR-130a both to the estrogen and HER2 pathways [114, 115], and miR-125 to HER2/erbb2 estrogen sensitive oncogene activation [116, 117]. These findings support the view that estrogen and HER2-dependent mechanisms can contribute to CS-induced lung carcinogenicity in females.…”
Section: Discussionmentioning
confidence: 62%
“…MiR-125b was selected and validated in vitro using UACC-812 cell (Additional file 13: Figure S2f, g). It was reported that ERBB2 was a target of MiR-125b in solid cancers [41, 48, 49]. Thus, expression of MiR-125b and ERBB2 in breast cancer was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In striking contrast, endometrial cancer tissue samples showed a significant decrease in fourteen tumor-suppressive miRNAs (Figure 1C). It is of interest to note here that all of the fourteen downregulated miRNAs, namely, miR-26a-5p [22, 23], miR-150-5p [24, 25], let-7f-5p [26, 27], miR-26b-5p [22, 23, 28], let-7c-5p [26, 27], miR-23b-5p [29-31], miR-126-3p [32], miR-125b-5p [33], hsa-miR-195-5p [34, 35], miR-424-5p [36, 37], hsa-miR-374a-5p [38-40], let-7a-5p [26, 27] , let-7e-5p [26, 27], and miR-125a-5p [41, 42] are known to have tumor-suppressive function in many cancers. Taken together with the upregulated genes, our results identify a panel of miRNAs that correlates with the tumor phenotype.…”
Section: Resultsmentioning
confidence: 99%